Estimating the impact of maternal anemia on low-birth-weight in Sub-Saharan African countries: propensity score matching analysis - Bezawit Melak Fente; Angwach Abrham Asnake; Yohannes Mekuria Negussie; Zufan Alamrie Asmare; Hiwot Altaye Asebe; Beminate Lemma Seifu; Mamaru Melkam; Meklit Melaku Bezie (BMC Pregnancy and Childbirth)
Abstract Background Low birth weight is the main cause of death, illness, and disability in infancy and childhood and has a lasting effect on adult healing here are several studies that indicate the correlation between low birth weight and anemia using an observational study based on the Demographic and Health Survey (DHS) but there are limited studies to show the direct effect of anemia on low birth weight. Therefore, we used the propensity score-matching (PSM) analysis to estimate the actual impact of maternal anemia on low birth weight babies. The study aims to reveal the effect of maternal anemia on low birth weight babies among reproductive-age women using propensity score matching analysis from the Demographic and Health Survey in Sub-Saharan Africa. Statement of the problem Pregnancy-related maternal nutritional deficiencies impact the fetus’s development, which in turn affects the newborn’s birth weight. The initiative to conduct this study is that most of the time mothers suffer from anemia and at the same time they deliver low birth weight children. LBW newborns had a 20-fold increased risk of morbidity and death compared to normal. Despite the burden of maternal anemia on low birth weight the direct relation with controlling other factors to show their direct cause and effect is not well studied. Method A community-based cross-sectional study was conducted based on the DHS data. We used the recent DHS data of 27 Sub-Saharan African countries. A total of 54,904 women with at least one birth in the last five years were considered. To estimate the impact of anemia on low birth weight, we used PSM analysis with a logit model using psmatch2 ate STATA command to find the average treatment effect on the population (ATE), treated and untreated. The quality of matching was assessed statistically and graphically. Sensitivity analysis was conducted to test the robustness of the PSM estimates using the Mantel- Haenszel test statistic. Results The prevalence of anemia in sub-Saharan Africa was 41.62%. The prevalence rate of low birth weight was 20.1%. In the PSM analysis, the difference in ATE of anemia on low birth weight was 13.0%. The difference in ATE among the treated group was 2.44% increased risk of low birth weight. The ATE in the treated group had a 12.1% increased risk of low birth weight. The estimates were insensitive to hidden bias and had a good quality of matching. Conclusion Anemia has a strong effect on low birth weight after matching treated and control groups of observed variables. Reducing maternal anemia for improved birth outcomes or increasing fetal birth weight requires treating anemia before and during the early stages of pregnancy, as well as providing regular nutrition instruction and counseling during routine ANC follow-up. The involvement of stakeholders in the treatment of anemia is warranted to decrease the rate of LBW and its late consequences.